2023
DOI: 10.1186/s12916-023-03085-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of provision of non-alcoholic beverages on alcohol consumption: a randomized controlled study

Hisashi Yoshimoto,
Kyoko Kawaida,
Shohei Dobashi
et al.

Abstract: Background The use of alcohol-flavored beverages not containing alcohol (hereinafter referred to as non-alcoholic beverages) is recommended to reduce alcohol consumption. However, it is unclear if this reduces excessive drinking. Objective To verify whether non-alcoholic beverages impact the alcohol consumption of excessive drinkers. Study design Single-center, open-label, randomized, parallel-group st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
2
5
1
Order By: Relevance
“…In this study, a 12-week intervention involving the provision of non-alcoholic beverages significantly increased non-alcoholic beverage consumption until 8 weeks after the completion of the intervention in both genders, which was consistent with our previous results [ 4 ]. Although it is well known that the absolute volume of alcohol consumption is higher in men than women [ 7 ], the present result suggests that providing non-alcoholic beverages increased their consumption to a similar extent in men and women.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, a 12-week intervention involving the provision of non-alcoholic beverages significantly increased non-alcoholic beverage consumption until 8 weeks after the completion of the intervention in both genders, which was consistent with our previous results [ 4 ]. Although it is well known that the absolute volume of alcohol consumption is higher in men than women [ 7 ], the present result suggests that providing non-alcoholic beverages increased their consumption to a similar extent in men and women.…”
Section: Discussionsupporting
confidence: 93%
“…One-hundred twenty-three people participated this study and all of them were randomized. After the randomization, we confirmed that there were no significant differences in basic attributes, as previously shown in our original study [ 4 ]. The baseline characteristics of participants stratified by gender are shown in Table 1 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…An on‐line study found the odds of selecting an alcohol‐free drink (NABs and soft drinks combined) increased when there was a greater proportion of alcohol‐free options [12]. A recent randomized controlled study found that social drinkers who received free NABs across 3 months had greater reduction in alcohol consumption than control group participants (who did not receive NABs) [13]. However, NAB use has also been associated with increased alcohol use and future intentions to consume alcohol [9, 14].…”
Section: Introductionmentioning
confidence: 99%